A new approach to English pedagogical grammar : the order of meanings - Tajino, Akira (London : Taylor and Francis, 2017)
'This book proposes Meaning-order Approach to Pedagogical Grammar (MAP Grammar) as a practical pedagogical approach in ESL and EFL contexts. Teaching grammar through an easy-to-understand three-dimensional model, MAP Grammar establishes the clause as the fundamental unit of English and interprets meaning units in the sentence, thus allowing visualizable association between individual grammar items. By focusing on the order of meaning (rather than the order of words) in a sentence, MAP Grammar also distills current descriptive sentence structures (typically taught as five or seven patterns) into one meaning-based sentence structure for teaching and learning. MAP Grammar makes syllabus design and teaching easier in the following ways:Visualizing English grammar in a clear model, allowing association between individual grammar items.Instruction relies on meaning, not metalanguage, making MAP Grammar easy to grasp.The meaning-based sentence structure allows teachers to address global errors, and learners to produce comprehensible English.'--Provided by publisher.
Keywords: Cognitive grammar; English language -- Grammar; Applied linguistics